Refinement of the basis and impact of common 11q23.1 variation to the risk of developing colorectal cancer. - Pittman, A; Webb, E; Carvajal-Carmona, L; Howarth, K; Bernardo, D; Broderick, P; Spain, S; Walther, A; Price, A; Sullivan, K; Twiss, P; Fielding, S; et al. (2008)
The common single-nucleotide polymorphism (SNP) rs3802842 at 11q23.1 has recently been reported to be associated with risk of colorectal cancer (CRC). To examine this association in detail we genotyped rs3802842 in eight independent case-control series comprising a total of 10 638 cases and 10 457 healthy individuals. A significant association between the C allele of rs3802842 and CRC risk was found (per allele OR = 1.17; 95% confidence interval [CI]: 1.12-1.22; P = 1.08 x 10(-12)) with the risk allele more frequent in rectal than colonic disease (P = 0.02). In combination with 8q21, 8q24, 10p14, 11q, 15q13.3 and 18q21 variants, the risk of CRC increases with an increasing numbers of variant alleles for the six loci (OR(per allele) = 1.19; 95% CI: 1.15-1.23; P(trend) = 7.4 x 10(-24)). Using the data from our genome-wide association study of CRC, LD mapping and imputation, we were able to refine the location of the causal locus to a 60 kb region and screened for coding changes. The absence of exonic mutations in any of the transcripts (FLJ45803, LOC120376, C11orf53 and POU2AF1) mapping to this region makes the association likely to be a consequence of non-coding effects on gene expression.